Salivary Markers Responses in the Post-Exercise and Recovery Period: A Systematic Review - Rafael Santos Neves; Marco Antônio Rabelo da Silva; Mônica A. C. de Rezende; Adriana Caldo-Silva; João Pinheiro; Amândio M. C. Santos (MDPI AG, 2023)
The use of saliva to monitor immune and hormonal responses in training, competitions, and during recovery is an easy and non-invasive alternative means of collecting samples compared to serum collection. Saliva can provide insight into a number of interesting biomarkers such as cortisol, testosterone, immunoglobulins, alpha-amylase, and melatonin, among others. High-intensity and exhaustive exercises, such as training or competition, provide variations in immune, protein and hormonal markers. An adequate recovery period, calming down, and recovery methods can contribute to a fast normalization of these markers, decreasing illness, as well as the likelihood of overtraining and injuries, but their effectiveness is still inconclusive. The aim of this review was to investigate the evidence of salivary markers in post-exhaustive exercise during the recovery period. This study is a systematic review from three electronic databases with studies from 2011 to 2021 within healthy humans. The search found 213 studies, and after applying the inclusion and exclusion criteria, while excluding duplicated studies, 14 studies were included in this review. The most cited salivary markers were cortisol and testosterone, as well as their ratio, alpha-amylase and IgA. Half of the studies applied a variety of recovery methods that showed controversial results over salivary markers' impact. However, they showed an impact on the markers from the exercise, which was still dependent on exercise intensity, methodology, and duration.